System dynamics simulation and regulation of human-water system coevolution in Northwest China - Wei, Li; Liu, Xiaopeng; Li, Xinyan; Gao, Haiyan (Frontiers in Ecology and Evolution, 2023)
The human-water system synergy in Northwest China has become more significant as the ecological civilization construction continues and the implementation of the 2030 Agenda for Sustainable Development in China proceeds. In this study, taking the Ningxia Hui Autonomous Region as a typical research region, the human–water system coevolution model was established by coupling SD (System Dynamics) model and coevolution model from the theoretical perspective of complex system synergies, to simulate the human-water system’s coevolution trends from 2010-2030 in this region. Five regulation schemes were then designed to enhance the synergy of the human-water system by adjusting sensitive decision variables. The results revealed that the supply to demand ratio of water and the synergy index of the human-water system obtained by the status continuation scheme would decline from 1.02 and 0.39 in 2020 to 0.81 and 0.35 in 2030, respectively, indicating the growing gap between water supply and demand and revealing the worsening human-water relationship. Under the comprehensive optimization scheme, the supply to demand ratio of water and the synergy index of the human-water system would be higher than under the other schemes, demonstrating a substantially improved human-water relationship. Hence, a comprehensive optimization regulation scheme is proposed. This scheme combines improving pro-environmental water consumption, adapting industrial structures, and carrying out water conservation and pollution prevention. This research renders a decision-making basis for regulating regional water resources and finding paths to developing a harmonious relationship between humans and water.